2014
DOI: 10.1103/physrevb.90.035432
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel-mediated coupling between antiferromagnetic thin films

Abstract: International audienceThe study, tailoring, and control of the coupling between magnetic layers triggered the development of spintronics and has been up to now focused on systems comprising at least one ferromagnetic layer. Here we present a system where two antiferromagnetic layers separated by an ultrathin tunnel barrier interact with each other. We have studied with neutron and x-ray diffraction two sets of Cr/MgO/Cr trilayers, with either thin (five monolayers or less) or thick (eight monolayers or more) M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In Cr/MgO/Cr tunnel junctions, they demonstrated tunnel magnetic coupling between the antiferromagnetic Cr layers through the MgO insulator. They showed that this coupling can be amplified thanks to the presence of resonant states exhibiting the same Δ 5 symmetry at the interface (Leroy et al, 2014).…”
Section: Tunnel Magnetoresistancementioning
confidence: 99%
“…In Cr/MgO/Cr tunnel junctions, they demonstrated tunnel magnetic coupling between the antiferromagnetic Cr layers through the MgO insulator. They showed that this coupling can be amplified thanks to the presence of resonant states exhibiting the same Δ 5 symmetry at the interface (Leroy et al, 2014).…”
Section: Tunnel Magnetoresistancementioning
confidence: 99%
“…Second, because up-and down-spin subbands are degenerate in antiferromagnets, the torque efficiency in AF-MTJs is much more robust against disorder than in F-MTJs. This shows that AF-MTJs, such as Cr/MgO/Cr [39,40], are solid candidates for the realization of spin transfer torque in antiferromagnets.…”
Section: Discussionmentioning
confidence: 94%
“…Such interfacial states have been identified in thin Fe(100)/MgO(100)/Fe(100) magnetic tunnel junctions [37,38] and, more recently, in Cr(001)/MgO(001)/Cr(001) antiferromagnetic tunnel junctions [39], associated with the surface states of Cr. Such states are believed to be responsible for tunneling magnetic coupling between the Cr electrodes [40] and could have an influence on spin transport.…”
Section: Beyond the Idealized Modelmentioning
confidence: 99%
“…Cr and Pt were deposited by MBE at about 0.3 nm/min, as checked by a quartz microbalance. The substrate was kept at 373 K during Cr deposition [31], whereas Pt was grown at room temperature (RT). Prior to Pt deposition, post-annealing was performed on selected Cr films at different temperatures (523 K, 873 K).…”
Section: Methodsmentioning
confidence: 99%
“…Chromium thin films are definitely easier to prepare than binary or ternary compounds (such as Mn2Au, IrMn, CuMnAs), because there is no need to satisfy stoichiometry constraints to obtain the AFM phase. Epitaxial single crystals can be obtained using molecular-beam epitaxy (MBE) [25,26] or magnetron sputtering [27] on top of several metals (e.g., Au [28], Ag [29], and Fe [30]) and oxides (e.g., MgO [31], SrTiO3 [32], TiO2 [33], and Al2O3 [34]). The structural and transport properties of thin epitaxial films have been addressed by different techniques (see, e.g., the synchrotron-based studies of charge-density, strain and spin-density waves reported in Refs.…”
Section: Introductionmentioning
confidence: 99%